A Temperature-Based Peak Power Capability Estimation Method for Lithium-Ion Batteries. (2017) - Jiang, Wu-Jie; Zhang, Ning; Li, Peng-Cheng; Chen, Nan
Abstract: The accurate estimation of the state of power (SoP) in battery systems is crucial for battery safety of hybrid electric vehicles and pure electric vehicles. Discharge or charge with large current might lead to significant rise of temperature to batteries. To improve the estimation accuracy of SoP for battery management systems, thermal characteristics of batteries during acceleration or deceleration of electric vehicles are considered. Considering the heat transfer from electrochemical reactions and joule heating to the air and consequently a corresponding rise of battery temperature, a model is established in Matlab/Simulink ® and integrated into the calculation process of SoP based on an 18650-type cylinder lithium-ion battery. The corresponding simulation results show that temperature limits have more influence than state of charge limits and terminal-voltage-based limits under high air temperature and high battery temperature. It is proven that multi-constraint SoP estimation method including the thermal effect has the potential to achieve higher prediction precision compared with the general SoP estimation methods.